Malaysian grown egusi (Citrullus lanatus) crop as potential feed stock for bio-energy - Bande, Yahaya Muhammad (2013)
The quest for newer renewable energy sources is an issue of major concern to many researchers world-over as a result of consistent world energy crisis on fossil-derived fuels, thus informs the need to diversify search for newer oil/energy crops. Egusi (citrullus lanatus) is a crop grown in African tropical countries. Works on the crop in Africa revealed that 50% is oil, utilizing only its seed kernel, being the main purpose of its cultivation in Africa. The crop was introduced in Malaysia, being a tropical country to observe its propagation adaptation and characterize it for biomass and biodiesel. A fundamental research initiated on the crop here in Malaysia involves planting on two different soil types and seasons to select suitability in terms of growth, crop maintenance and harvest, and finally processing the fruit to obtain seeds. On a 200m2 experimental plot, a harvest of 1,125 fruits was made, producing 45.56kg of seeds during dry season, with a harvest of 137 fruits during wet season producing 1.373kg of seeds. Physical and mechanical properties of fruits were determined to guide development of machines for production, harvest and post-harvest operations and mechanized seed extraction devices from the harvested fruits. Mechanical properties of fruits were similar irrespective of the season grown, but there were smaller and fewer fruits during wet season. Physical and mechanical properties of seeds were determined as a guide to the design and development of devices on the mechanization of oil extraction from seeds since using solvent is uneconomical and impracticable for large oil production from egusi. There was no difference in the properties of seeds by season. Values of physical and mechanical properties were determined at four different moisture contents (7.11%,14.65%, 28.07% and 38.70% w.b) the mean values of properties determined for seeds at 38.70% were length (15.21±1.04mm), thickness (2.56±0.27mm), width (8.59±0.53mm),angle of repose (33.63o±1.58), hardness (vertical 51kg±1.08; horizontal 121.3±2.65kg) and coefficient of friction on different surfaces. The heating values of its biomass components (roots, stalk and leaves), lowest of which was the roots, with 11.9MJ/kg and the highest value recorded was 31.16MJ/kg for seed kernel, at 7.45% w.b moisture content, with egusi whole seed oil methyl ester (EWSOME B100) generating 45.72MJ/kg with the pure diesel oil (PDO), generating 47.95MJ/kg. Ultimate analysis was conducted to determine the elemental composition of its biomass, roots (C 40.92%; H 4.15%; N 1.54%; S 0.17%; O 52.22%), stalk (C 39.73%; H 5.11%; N 1.21%; S -0.07%; O 54.02%) and leaves (C 39.18%; H 4.88%; N 1.92%; S -0.12%; O 54.15%) for determination of elemental composition of burning the biomass. Biomass, oil and biodiesel prospect of the crop in Malaysia was also estimated as additional source of oil/energy to the well-established oil palm. Oil extracted from 800g dehulled and whole seeds produced 480ml and 380ml respectively. The extracted oil from both whole seed (EWSO) and dehulled seeds (EDSO) were synthesized and characterized for their respective fuel properties. A basic engine performance test was conducted on both biodiesels using B5, and reference was made to engine performance on pure diesel oil (PDO). The results showed that EWSOME B5 performed better than EDSOME B5, with power and torques 2% less than PDO but specific fuel consumption was 4% more than PDO. Economic implication of semi-mechanizing the production of biomass and biodiesel from egusi plantation was estimated based on the available data on basic farm implements and costs, using the most productive season in Malaysia. Cultivating egusi over the experimental plot during current work was evaluated to cost RM 1,451 only.